2003
DOI: 10.1080/1042819031000119262
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Febrile Neutropenia among Patients with Intermediate-grade non-Hodgkin's Lymphoma Receiving CHOP Chemotherapy

Abstract: We sought to identify risk factors associated with the time to febrile neutropenia in patients with intermediate-grade, non-Hodgkin's lymphoma (NHL) who were receiving treatment with CHOP chemotherapy. Data were collected from 12 community and academic oncology practices participating in the Oncology Practice Pattern Study between 1991 and 1999. We reviewed the medical records of 577 intermediate-grade NHL patients who received initial CHOP chemotherapy and evaluated risk factors associated with time to first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
162
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 210 publications
(181 citation statements)
references
References 16 publications
16
162
0
3
Order By: Relevance
“…[4][5][6] Major risk factors for the development of FN include older age, comorbid conditions, the type of cancer, and the type and number of myelosuppressive chemotherapy agents used. [5][6][7] FN represents a lifethreatening complication that requires urgent evaluation for the identification and treatment of documented or presumed infection. 8 Infection in the neutropenic cancer patient often can be difficult to identify because of the lack of neutrophils and associated clinical symptoms and signs.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%
“…[4][5][6] Major risk factors for the development of FN include older age, comorbid conditions, the type of cancer, and the type and number of myelosuppressive chemotherapy agents used. [5][6][7] FN represents a lifethreatening complication that requires urgent evaluation for the identification and treatment of documented or presumed infection. 8 Infection in the neutropenic cancer patient often can be difficult to identify because of the lack of neutrophils and associated clinical symptoms and signs.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%
“…In addition, previous risk modeling studies have suggested an association between greater than 80% ARDI and increased risk of a febrile neutropenic event. 8,9 Hospitalization for febrile neutropenia was determined from the patient's medical record. Time to first hospitalization for febrile neutropenia was defined as the number of days from the start of Cycle 1 chemotherapy to the day that the first hospitalization for febrile neutropenia occurred.…”
Section: Treatment Characteristics and Outcomesmentioning
confidence: 99%
“…In addition, to our knowledge, none of these models have been validated. [7][8][9][10][11] Furthermore, previous risk modeling efforts have provided limited information regarding the risk and timing of the first hospitalization for febrile neutropenia.…”
mentioning
confidence: 99%
“…[5][6][7] These dose modifications often are implemented during the first cycles of chemotherapy, because neutropenic events often occur early during the course of chemotherapy. 8,9 Treatment response frequently depends on the delivery of standard chemotherapy doses, and modifications in dosing may threaten complete response rates and reduce survival. 10 -15 Thus, caregivers face a challenge in maintaining adequate chemotherapeutic doses while managing neutropenic complications.…”
mentioning
confidence: 99%